Encountering the Urban Crisis: The Gezi Event and the Politics of Urban Design. Issue 2 (2nd July 2016) - Batuman, Bülent; Baykan, Deniz Altay; Deniz, Evin
Abstract : This article addresses an experimental urban design studio conducted in Bilkent University in Ankara, which problematized the protests that initially started in Gezi Park in Istanbul and shook Turkey in the summer of 2013. As will be argued in detail below, we claim that the Gezi event represents an urban crisis. The particular event was the rapid escalation of a small protest against the destruction of a public space into a nationwide anti-government insurrection. But it also represented a larger urban crisis: the increasing influence of neoliberalism on the city, as the protests were the outcome of a period marked by zealous commodification of urban space. In both instances, such urban conflicts have to be addressed by urban designers, since they produce the renewal projects that gentrify urban spaces and, at the same time, seek possible alternatives for a better urban environment.